Incidence, Risk Factors, and Outcomes of Postoperative Atrial Fibrillation after Cardiac Surgery - Musaad AlHamzah; Shirin Alokayli; Ghadah A. Alarify; Abdullah Alghamdi; Fahad Alsultan; Naif Alsulais; Kazi Nur Asfina; Abdelrahman Zamzam; Walid Alayadhi; Wael Alqarawi (Journal of Nature and Science of Medicine)
Objective: Postoperative atrial fibrillation (POAF) is a known complication after cardiac surgery. This study investigated the incidence, perioperative outcomes, and predictors of POAF. Methods: We conducted a retrospective review of all eligible patients undergoing cardiac surgery procedures at King Khalid University Hospital, Riyadh, Saudi Arabia, between April 2015 and June 2021. Prespecified demographic, perioperative, and comorbidity data were collected, and summary statistics were done. Results: The incidence of POAF was 10.8% (114/1053 patients). Most patients had POAF detected in the first 72 h, except those who underwent septal defect repair procedures. Patients who developed POAF had significantly higher rates of complications, including major adverse cardiovascular events, pneumonia, bleeding and shock, acute kidney injury, and congestive heart failure (all had a P ≤ 0.005). Advanced age and increased body mass index were the preoperative predictors of POAF. Furthermore, undergoing coronary artery bypass grafting (CABG), valve replacement surgery, or a combined procedure were also predictors of POAF. Conclusion: POAF after cardiac surgery is a common complication with increased risks of significant complications. Efforts to prevent POAF incidence are required through prediction and preventive measures. More studies are needed to determine if early detection and prompt treatment could mitigate the clinical sequelae of POAF.